Comparison between various indices of exposure to traffic-related air pollution and their impact on respiratory health in adults. Issue 10 (18th January 2008) - Cesaroni, G; Badaloni, C; Porta, D; Forastiere, F; Perucci, C A
Abstract : Objective: To evaluate the association of different indices of traffic-related air pollution (self-report of traffic intensity, distance from busy roads from geographical information system (GIS), area-based emissions of particulate matter (PM), and estimated concentrations of nitrogen dioxide (NO2 ) from a land-use regression model) with respiratory health in adults. Methods: A sample of 9488 25–59-year-old Rome residents completed a self-administered questionnaire on respiratory health and various risk factors, including education, occupation, housing conditions, smoking, and traffic intensity in their area of residence. The study used GIS to calculate the distance between their home address and the closest high-traffic road. For each subject, PM emissions in the area of residence as well as estimated NO2 concentrations as assessed by a land-use regression model (R 2 value = 0.69), were available. Generalised estimating equations (GEE) were used to analyse the association between air pollution measures and prevalence of "ever" chronic bronchitis, asthma, and rhinitis taking into account the effects of age, gender, education, smoking habits, socioeconomic position, and the correlation of variables for members of the same family. Results: Three hundred and ninety seven subjects (4% of the study population) reported chronic bronchitis, 472 (5%) asthma, and 1227 (13%) rhinitis. Fifteen per cent of subjects reported living in high traffic areas, 11% lived within 50 m of a high traffic road, and 28% in areas with estimated NO2 greater than 50 μg/m 3 . Prevalence of asthma was associated only with self-reported traffic intensity whereas no association was found for the other more objective indices. Rhinitis, on the other hand, was strongly associated with all traffic-related indicators (eg, OR = 1.13, 95% CI: 1.04 to 1.22 for 10 μg/m 3 NO2 ), especially among non-smokers. Conclusions: Indices of exposure to traffic-related air pollution are consistently associated with an increased risk of rhinitis in adults, especially among non-smokers. The results for asthma are weak, possibly due to ascertainment problems.